Strain transfer analysis of embedded fiber bragg grating strain sensor - Sun, L.; Hao, H.; Zhang, B.; Ren, X.; Li, Jun (ASTM International, 2016)
Due to the difference in the physical and mechanical properties between the optical fiber, protective layer, adhesive layer, and the host material, the strains measured by a fiber Bragg grating (FBG) sensor may not be the actual strains of the host material, which impedes the reliable applications of FBG sensors. To overcome this problem, in this paper, the strain transfer formula was derived by using elastic analysis, the shear-lag method, and several reasonable assumptions taking into account temperature variations and nonaxial stresses, which was an improvement to an existing study (Li, H. N., Zhou, G. D., Ren, L., and Li, D. S., "Strain Transfer Analysis of Embedded Fiber Bragg Grating Sensor Under Nonaxial Stress," Optic. Eng., Vol. 46, No. 5, 2007, 054402). The analytical results were validated by simulating the behavior of a bare optical fiber through finite element analysis. The data enabled the identification of the parameters that influence the strain transfer from the host material to the embedded FBG sensors and the impact of the temperature variation and sensor alignment angle on the measurement accuracy. This work provided additional knowledge for the improvement of the existing strain transfer theory of FBG sensors in order to achieve a more accurate strain measurement with this sensing technology.